The Identity of “Islamic Fashion” / Asliza Aris, Suzlee Ibrahim and Hasma Ahmad - Aris, Asliza; Ibrahim, Suzlee; Ahmad, Hasma (Universiti Teknologi MARA, 2018)
This study looks at the issues in fashion where the term “Islamic fashion” is widely used for Muslimah’s garments. “Islamic fashion” is interpreted largely by fashion designers with the understanding that the garments should clothe the body and hair of the wearer. The issue raised is whether the execution of “Islamic fashion” is syariah compliance, which corresponds to the Al-Quran and Sunnah. Samples of fashion garments are collected, analysed and compared to Islamic dress criteria, Malay wear and global fashion trend. Perhaps, the term, “Islamic fashion” is used commercially as fashion statement due to its “modest look” parallel to Malaysian society.